Mapa conceptual en salud y propiedad intelectual en Centroamérica y la República Dominicana. - García Delgado, Beatriz M.; Silva, Ana Paula; de Rodriguez, Juana M. (Pan American Journal of Public Health, 2019)
Objective. The objective of this study is to prepare a "Concept Map on Health and Intellectual Property in Central America and the Dominican Republic" in order to help identify the main access barriers to health, especially medicines, and to guide state authorities toward actions to improve the efficiency and effectiveness of policies. Methods. The report "Concept Map on Public Health and Intellectual Property, Regional Perspective: Central America and the Dominican Republic" was analyzed. Then the knowledge generation and management methodology was applied and a search strategy was identified to recover the information for preparation of the concept maps. Results. The legal framework and institutional structure, as well as policies, programs, plans, and strategies for health and intellectual property, were identified. A set of barriers that hinder access to medicines was also identified, as well as solutions to overcome them. Conclusions. In Central America and the Dominican Republic, health strategies, policies, programs, and plans are in place, but unfortunately their scope and degree of dissemination is uneven. This, together with social and economic factors, explains why health inequity persists between and within countries. The identified barriers to access to medicines included the expansion and strengthening of the rights of pharmaceutical patent-holders, problems with implementing the flexibilities of the Agreement on Trade-related Aspects of Intellectual Property Rights, pricing policies, and strict regulatory standards.